Dorsal Metatarsal Closed Wedge Osteotomy in the Treatment of Freiberg’s Disease: A Prospective Observational Study - Öztürk, Vedat; Bilgili, Mustafa Gökhan; Baca, Emre (Zeitschrift für Orthopädie und Unfallchirurgie, 2024)
The aim of this study was to prospectively evaluate the clinical and radiological results of dorsal metatarsal closed wedge osteotomy and headless screw fixation in the surgical treatment of Freiberg’s disease.Thirty-four patients who were treated with dorsal metatarsal closed wedge osteotomy (DMCWO) for Freiberg’s disease between February 2018 and March 2022 were included in the study. Patients were staged according to the classification system described by Smillie. Clinical outcomes were evaluated using the American Orthopedic Foot and Ankle Society’s (AOFAS) lesser metatarsophalangeal-interphalangeal scale, the visual analog scale (VAS), the range of motion (ROM) of the metatarsophalangeal (MTP) joint, and a subjective patient satisfaction questionnaire. For radiological evaluation, the amount of preoperative shortening of the involved metatarsal, the amount of metatarsal shortening developed after osteotomy, and radiological recovery times were recorded.Thirty-two (94.1%) of the patients were female, and two (5.9%) were male. The average postoperative follow-up period for patients was 33.7 months (range: 24 months to 41 months). The mean AOFAS scores increased from 53.24 to 86.26 (p < 0.01). The mean VAS scores decreased from 8.59 to 1.79, and it was observed that the patients’ pain improved significantly (p < 0.01). The mean ROM of the MTP joint increased from 48.76 degrees to 70.76 degrees (p < 0.01). An average of 2.5 mm (range 1 mm to 4.1 mm) of shortening of the metatarsal length developed postoperatively (p < 0.01). Arthrosis developed in 1 case (2.9%), and transfer metatarsalgia developed in 2 cases (5.8%).DMCWO is an effective treatment for both the early and advanced stages of symptomatic Freiberg’s disease, leading to high patient satisfaction.
Keywords: Freiberg disease; metatarsal osteotomy; metatarsalgia; osteochondrosis